Evaluation of tonsillectomy in the treatment of SAPHO syndrome: past evidence and future directions - Gan, Wen-Yuan; Ren, Ben-Hong; Zhang, Qing-Ping; Wang, Yi (Frontiers in Medicine, 2025)
Synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome is a rare aseptic inflammatory clinical syndrome characterized by widespread skin lesions and bone-joint lesions. The underlying mechanisms remain unclear, making it difficult to treat. Currently, drug-based symptomatic treatment is the main approach, but symptoms often recur or worsen when medications are reduced or discontinued. Recently, there have been increasing reports of the significant therapeutic effects of tonsillectomy in treating SAPHO syndrome. This paper reviews the past evidence on the use of tonsillectomy for SAPHO syndrome by searching PubMed, Google Scholar, Web of Science, Embase, Scopus, CNKI, and Wanfang databases using the keywords “SAPHO syndrome and tonsillectomy.” It also discusses the potential mechanisms of tonsillectomy in treating SAPHO syndrome, aiming to provide new treatment methods for SAPHO syndrome.